2020
DOI: 10.1186/s12974-020-01777-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload contributes to general anaesthesia-induced neurotoxicity and cognitive deficits

Abstract: Background: Increasing evidence suggests that multiple or long-time exposure to general anaesthesia (GA) could be detrimental to cognitive development in young subjects and might also contribute to accelerated neurodegeneration in the elderly. Iron is essential for normal neuronal function, and excess iron in the brain is implicated in several neurodegenerative diseases. However, the role of iron in GA-induced neurotoxicity and cognitive deficits remains elusive. Methods: We used the primary hippocampal neuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 48 publications
4
99
3
Order By: Relevance
“…Our results of western blot further proved that Sev significantly increased the expression of FtL and downregulated the expression of TfR1, indicating that Sev induced the dysfunction of iron metabolism in cortex and hippocampus as shown in Figure 3 . Wu [ 23 ] recently also confirmed that iron overload was involved in the pathogenesis of sevoflurane-induced neurotoxicity and cognitive deficits indicating that Sev-induced neurotoxicity and iron metabolism disorders are closely related. Too much iron initiated the oxidative stress pathway and produced amount of ROS, especially in cortex through the Fenton reaction, and further damaged the function of mitochondrial via decrease the MMP, inducing cell apoptosis via Bcl2/Bax pathway as shown in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results of western blot further proved that Sev significantly increased the expression of FtL and downregulated the expression of TfR1, indicating that Sev induced the dysfunction of iron metabolism in cortex and hippocampus as shown in Figure 3 . Wu [ 23 ] recently also confirmed that iron overload was involved in the pathogenesis of sevoflurane-induced neurotoxicity and cognitive deficits indicating that Sev-induced neurotoxicity and iron metabolism disorders are closely related. Too much iron initiated the oxidative stress pathway and produced amount of ROS, especially in cortex through the Fenton reaction, and further damaged the function of mitochondrial via decrease the MMP, inducing cell apoptosis via Bcl2/Bax pathway as shown in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently completed the work demonstrating that sevoflurane causes brain iron deficiency, inhibits myelin development, and induces cognitive impairment in the offspring of pregnant mice [ 20 ]. However, our recent and others study have shown that Sev can cause cognitive impairment by inducing the iron overload in brain in 12-month-old mice [ 19 , 23 ]. This suggests that Sev has different effects on iron metabolism in mice of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…BAY 11-7082 (20 mg/kg) or PBS (vehicle) was intraperitoneally administered to the pups 30 min before gas inhalation [ 18 , 19 ]. Sevoflurane anesthesia was induced by placing the rat pups in an anesthetizing chamber delivering 3% sevoflurane for 2 h daily for three consecutive days [ 20 , 21 ]. In the control condition, 30% O 2 was delivered at the same flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…In this process, iron accumulation ( Shang et al, 2020 ) and administration of iron-bound, rather than iron-free TF, promote erastin-induced ferroptosis ( Gao et al, 2015 ). On the contrary, using some iron chelators [e.g., DFP ( Wu et al, 2020 ), DFO ( Wu et al, 2018 ; Chen et al, 2020 ), and BPS ( Codenotti et al, 2018 )] may suppress ferroptosis and provide a potential therapeutic approach for diseases. In fact, there are some iron-chelating agents under clinical development for the treatment of cancers [for review see Brown et al (2020) ].…”
Section: Discovery and Mechanisms Of Ferroptosismentioning
confidence: 99%